Exploring The Teacher’s Roles and Practice in Promoting Students’ Engagement: A Focus on Non-English Major Students - Ratih Pertiwi; Titin Rahmiatin Rahim; Muflihun Muflihun (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study explores the roles and practices of an English for Specific Purposes (ESP) teacher in fostering student engagement among non-English major students in higher education. Employing a qualitative descriptive approach, data were collected through questionnaires and semi-structured interviews with a teacher at Muhammadiyah University of Kendari. The findings reveal that the teacher’s effectiveness stems from a combination of pedagogical, social, and professional competencies. Strategies employed to enhance engagement include creating a warm and inclusive classroom environment, tailoring teaching methods to accommodate diverse student proficiency levels, and implementing effective time management practices. These approaches significantly improved students’ confidence, participation, and language acquisition outcomes. The study also identified challenges such as limited course duration, which restricts long-term assessment, and occasional student reluctance in group activities. To address these challenges, the teacher relied on adaptive strategies and emphasized the importance of professional development programs, such as the Inter-disciplinary Teacher Collaboration (ITC) program, which provided new insights into effective ESP instruction. The study sheds light on the importance of collaborative learning, scaffolding techniques, and tailored instruction in meeting the specific linguistic and professional needs of ESP students. This research contributes to the understanding of ESP pedagogy by offering practical and theoretical insights into effective teaching practices. It highlights the critical role of teacher agency in shaping engagement and learning outcomes. The findings provide a foundation for improving ESP instruction and call for future research to explore longitudinal impacts, comparative studies, and the integration of technology in ESP classrooms.